2001
DOI: 10.4315/0362-028x-64.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Acid Sprays Reduce Bacterial Pathogens on Cold Beef Carcass Surfaces and in Subsequently Produced Ground Beef

Abstract: Organic acids have been shown to be effective in reducing the presence of pathogenic bacteria on hot beef carcass surfaces; however, application for decontaminating chilled carcasses has not been fully evaluated. In this study, a postchill, 30-s lactic acid spray (500 ml of 4% L-lactic acid, 55 degrees C) was applied onto outside rounds that had been contaminated with Escherichia coli O157:H7 and Salmonella Typhimurium, subsequent to prechill hot carcass treatments consisting of water wash alone or water wash … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
48
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(55 citation statements)
references
References 27 publications
5
48
1
1
Order By: Relevance
“…Results similar to those obtained by us were published by Castillo et al (2001), in a study on the efficacy of Salmonella Enteritidis reduction methods from the surface of chilled cattle carcasses, which showed a reduction between 1.6-1.9 log when using 2% lactic acid. Similarly, Harris et al (2006) showed a reduction of E. coli and Salmonella spp.…”
Section: The Decontamination Effect Of Organic Acid Solutions On Salmsupporting
confidence: 78%
“…Results similar to those obtained by us were published by Castillo et al (2001), in a study on the efficacy of Salmonella Enteritidis reduction methods from the surface of chilled cattle carcasses, which showed a reduction between 1.6-1.9 log when using 2% lactic acid. Similarly, Harris et al (2006) showed a reduction of E. coli and Salmonella spp.…”
Section: The Decontamination Effect Of Organic Acid Solutions On Salmsupporting
confidence: 78%
“…10 6 CFU or with shedding in naturally infected calves. Johnson et al (26) also found little change in O157 antibody titers in calves administered 10 7 CFU, while at a dose of 10 10 CFU there was an increase but the antibodies did not influence the reinfection of the animal with the same strain. Similarly, a horse serum albumin-O157 antigen conjugate elicits a specific systemic antibody response in BALB/c mice but does not impact intestinal colonization following oral inoculation with the pathogen (9).…”
Section: Discussionmentioning
confidence: 92%
“…Epidemiological data indicate that waterborne and person-to-person transfer are also important modes of transmission (33). The association of E. coli O157:H7 with cattle and bovine products has focused research on slaughter practices and decontamination of carcasses in order to circumvent this zoonosis (1,6,7,27).…”
mentioning
confidence: 99%
“…Organic acids are used to perform the acid wash. The organic acids generally used are acetic [25,26], citric [27], lactic [25][26][27][28] and propionic acids [26]. The acid wash step is very important to remove the bacteria carried along on the carcasses.…”
Section: Journal Of Food Chemistry and Nanotechnology | Volume 3 Issumentioning
confidence: 99%